A new species of Lachesilla Westwood (Psocoptera: Lachesillidae) in the andra group with a proposed classification of the andra group - Mockford, Edward L.; Aldrete, Alfonso N. García (Zootaxa, 2010)
We describe Lachesilla texana Mockford and García Aldrete, n. sp., with populations in northeastern Mexico, central and southern Texas, and Great Smoky Mountains National Park, Tennessee. Several minor differences are noted between the Smoky Mountains and the Texas-Mexican populations. We assign the new species to the andra group (García Aldrete 1974) and in order to place it within this large and complex species group, we propose a classification of the group with designation of four subgroups based primarily on male external genitalic and paragenitalic structures. Probable apomorphies are noted for each of the subgroups.